2008
DOI: 10.1002/anie.200800677
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Peptides Bearing a Side‐Chain Tail: A Tool to Model the Structure and Reactivity of Protein Zinc Sites

Abstract: A recent bioinformatics study has evaluated to about 1000 (or ca. 3 % of the total protein number) the number of human proteins possessing a tetracysteinate zinc site.[1] These sites were initially presumed to have a structural role because they were associated to zinc finger proteins, [2] where they fold the protein chain in a conformation suitable for its binding to DNA. They were later found in several proteins and enzymes involved in demethylation processes, such as the DNA repair protein Ada [3] and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 18 publications
2
55
0
Order By: Relevance
“…We observed that a cyclic peptide was indeed more efficient than its non-cyclic analogue to control the coordination properties and to constrain the backbone in a unique conformation around zinc. [16] The work described herein validates this approach, which allows the correct fold of the treble-clef zinc fingers to be reproduced with a minimal set of amino acids. Moreover, as observed for the models of the Hsp33 zinc site, the hydrogen-bond network between the backbone amides and the zinc-binding cysteinate sulfur atoms is excellently reproduced in these model complexes.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We observed that a cyclic peptide was indeed more efficient than its non-cyclic analogue to control the coordination properties and to constrain the backbone in a unique conformation around zinc. [16] The work described herein validates this approach, which allows the correct fold of the treble-clef zinc fingers to be reproduced with a minimal set of amino acids. Moreover, as observed for the models of the Hsp33 zinc site, the hydrogen-bond network between the backbone amides and the zinc-binding cysteinate sulfur atoms is excellently reproduced in these model complexes.…”
Section: Discussionsupporting
confidence: 53%
“…[16] This design allows the metallated peptides to fold in a defined conformation suitable to NMR structural characterisation, which is rarely the case for small, linear, peptide-based models. These peptides almost perfectly reproduce both the first coordination sphere and the hydrogen-bond network of the ZnA C H T U N G T R E N N U N G (Cys) 4 site of Hsp 33.…”
Section: The Origin Of This Stabilisation Is As-a C H T U N G T R E Nmentioning
confidence: 99%
“…The fold of the backbone, the relative orientation of the cysteine side-chains and the hydrogen bonds involving the cysteine sulfur atoms in the protein PerR are reproduced by this model. The second peptide, Zn·L HSP , [28] was designed to mimic the ZnA C H T U N G T R E N N U N G (Cys) 4 site of Hsp33. [24] Here again, the model complex reproduces almost perfectly the fold of the protein around the zinc ion.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of the signal could be perfectly fitted by a single exponential. [28] The observed first-order rate constant k obs varies linearly with [H 2 O 2 ], which shows that the oxidation follows a second-order kinetic law,…”
Section: Mechanism Of the Oxidation Of Zna C H T U N G T R E N N U N mentioning
confidence: 92%
See 1 more Smart Citation